Phenometric predictors of Pontederia crassipes biomass under natural conditions in the Paraná River - Casco, Sylvina Lorena (2024)
The water hyacinth, Pontederia crassipes, is a free-floating aquatic plant native to South America, which has colonized tropical rivers in several continents and has become dominant in floodplains. Aim: This study aimed to evaluate the relationship between leaf length and leaf biomass (as an indirect phenometric estimation) and to compare the accuracy of the indirect phenometric estimation (which is a non-destructive method) with that of the direct estimation of aboveground biomass (which is destructive). Methods: Pontederia crassipes green leaves of all sizes were collected from a floodplain lake of the Paraná River (Argentina). The leaves were oven-dried in the laboratory to obtain the constant dry weight. To determine the accuracy the indirect phenometric estimation was compared with the direct estimation of aboveground biomass. The relationship between leaf weight and leaf length was evaluated by regression analysis. The length of the 279 green leaves collected ranged between 7 and 115 cm. Results: The non-destructive method was a good predictor of leaf biomass (R2 = 0.87 p < 0.0001). No significant differences were found between the dry weight obtained directly and that estimated by the indirect method. Conclusions: Our results suggest that leaf length is a good attribute to estimate the aboveground biomass of P. crassipes. This method can contribute to diminish the impact of the direct method of harvest of P. crassipes and can be applied in experimental studies aimed to determine the leaf life span and primary productivity of P. crassipes clones.